2011
DOI: 10.1007/s11064-011-0508-0
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Progestogens in Regulating Matrix Metalloproteinase Activity in Macrophages and Microglial Cells

Abstract: Although the systemic effects of progestogens have been extensively studied, little is known in regards to the cellular effects of these compounds. Using a cellular model for vascular (macrophages) and brain (microglial) cells, we studied the effects of various progestogens, either alone or in combination with 17β-estradiol (E(2)) on the activity of matrix metalloproteinase-9 (MMP-9), a proteolytic enzyme involved in vascular remodeling and plaque destabilization in cardiovascular events, blood-brain barrier b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
2
6
1
Order By: Relevance
“…Further, progesterone decreases reactive oxygen species through its effects on mitochondria in multiple tissue types, including the brain [43,44]. Progesterone also modulates microglial cytokine expression [9,10,11,12]. In the present study, progesterone decreased brain edema, microglial proliferation/macrophage recruitment, and cytokine expression, while hematoma volume was constant.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Further, progesterone decreases reactive oxygen species through its effects on mitochondria in multiple tissue types, including the brain [43,44]. Progesterone also modulates microglial cytokine expression [9,10,11,12]. In the present study, progesterone decreased brain edema, microglial proliferation/macrophage recruitment, and cytokine expression, while hematoma volume was constant.…”
Section: Discussionsupporting
confidence: 50%
“…Indeed, when exogenous progesterone was administered following ICH, male rats showed decreased brain edema and improved neurobehavioral outcome [8]. Progesterone plays many roles in the central nervous system and is known to modulate neuroinflammation through effects on microglia [9,10,11,12], which are thought to be important in the post-ICH inflammatory response [13]. …”
Section: Introductionmentioning
confidence: 99%
“…The present study investigated the expression of MMP-9 in C6 glial cells treated with MPA. Several reports have demonstrated that MPA can alter MMP-9 levels, where levels are increased in macrophages and, alternatively, reduced in BV2 microglial, endometrial cancer, and primary amnion epithelial cells (Di Nezza et al, 2003;Hwang-Levine et al, 2011;Allen et al, 2019). Consistent with these reports, we found that MMP-9 protein expression and enzymatic activity is lowered by treatment with MPA.…”
Section: Discussionsupporting
confidence: 91%
“…MMP-9 is critical for cellular processes involved in learning and memory, as it regulates dendritic spine morphology, maintains late-phase long term potentiation (LTP), and controls postnatal brain development (Nagy et al, 2006;Michaluk et al, 2011;Kamat et al, 2014;Gorkiewicz et al, 2015;Reinhard et al, 2015;Kaczmarek, 2016). MPA has also been shown to alter MMP-9 activity and production in BV2 microglial, cancer, and epithelial cells (Di Nezza et al, 2003;Hwang-Levine et al, 2011;Allen et al, 2019). Additionally, the secretion of MMP-9 was found to be negatively impacted by MPA in the aforementioned cell types (Deb and Gottschall, 1996;Deb et al, 2003;Hwang-Levine et al, 2011;Allen et al, 2019).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation